Acute Compartment Syndrome in Orthopedics: Causes, Diagnosis, and Management - Hasnain Raza; Anant Mahapatra (Advances in Orthopedics)
Almost all orthopaedic surgeons come across acute compartment syndrome (ACS) in their clinical practice. Diagnosis of ACS mostly relies on clinical findings. If the diagnosis is missed and left untreated, it can lead to serious consequences which can endanger limb and life of the patient and also risk the clinician to face lawsuits. This review article highlights the characteristic features of ACS which will help an orthopaedic surgeon to understand the pathophysiology, natural history, high risk patients, diagnosis, and surgical management of the condition.